An Interactive Domino Card in Teaching Past Tense - Akbar Cahya Nugraha; Muhamad Sofian Hadi (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2021)
The aim of this study was to know the significance and the effectiveness of Domino Card in Teaching Past Tense in students' grammar skills. The study was conducted in SMK Pariwisata Puspa Wisata PGRI Serpong. XII APH 2 was a sample of class which consists of 30 students. The method of this study used a quantitative method with a pre-experimental research design. Pre-test and post-test were used to collect the data. The result of the total students’ pre-test scores is 1590 with an average score of 53, meanwhile, the post-test scores are 2400 with an average of 80. The calculation results of pre-test and post-test used t-test and indicated that the t-count was 14,1 with t-table was 1,71 at the 0,05 significance level. So, this indicates that the alternative hypothesis is accepted and the null hypothesis is rejected. This means that using Domino Card in Teaching Past Tense is effective. Keywords: Domino Card, Teaching Past Tense, method, grammar